From the History of Interrelations between Psychology and Metaphysics - Naghdyan, Ruben (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
In the second half of the XX century the studies on philosophy of science showed that the science is based on certain metaphysical assumptions. We can therefore assume that psychology, as a science, in some way must also be connected with the metaphysical postulates and principles determining the origin and development of the psychic. This fact is in contradiction with the point that in the methodology of modern psychology, as we know, there was no place for the metaphysical approach after the methodological transformation of L. S. Vigotsky. However, in XIX and early in XX centuries the situation was quite different. Among European psychologists, such as I. Herbart, V. Wundt, W. James and K. Jaspers, in particular, turned to metaphysics. By the end of the XIX century the interest towards metaphysics increased in Russia, too. The significant role of metaphysical ideas in the study of psychic was recognized by V. Soloviev, S. Troubetzkoy, N. Grot, S. Frank, P. Florensky, G. Chelpanov and others. However, as mentioned above, after Marxism had been attracted in psychology by L. S. Vigotsky as its methodological basis, metaphysics was banished from psychology as a field of idealistic knowledge. It was only late in XX century that such scholars as V. M. Allakhverdov, V. P. Zinchenko, A. I Mirakyan, A. V. Petrovsky and M. G. Yaroshevski again demonstrated the possibility and necessity of application metaphysical ideas and concepts in psychology.